2010
DOI: 10.1371/journal.ppat.1000742
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of xCT by KSHV-Encoded microRNAs Facilitates KSHV Dissemination and Persistence in an Environment of Oxidative Stress

Abstract: Upregulation of xCT, the inducible subunit of a membrane-bound amino acid transporter, replenishes intracellular glutathione stores to maintain cell viability in an environment of oxidative stress. xCT also serves as a fusion-entry receptor for the Kaposi's sarcoma-associated herpesvirus (KSHV), the causative agent of Kaposi's sarcoma (KS). Ongoing KSHV replication and infection of new cell targets is important for KS progression, but whether xCT regulation within the tumor microenvironment plays a role in KS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 69 publications
5
109
1
Order By: Relevance
“…Thus far, miRNA studies have been constrained by sensitivity limits for detection of individual miRNAs and for the discovery of miRNA-target interactions. Targets with functions that seem to befit the biology of B cell development, endothelial cell differentiation, and KSHV (such as BACH1, xCT, MAF, and others) have been individually validated (132)(133)(134). These are by no means the only targets, and it is anticipated that additional targets will be identified in the future.…”
Section: Viral Mirnas Support Viral Infection and Latent Persistencementioning
confidence: 99%
“…Thus far, miRNA studies have been constrained by sensitivity limits for detection of individual miRNAs and for the discovery of miRNA-target interactions. Targets with functions that seem to befit the biology of B cell development, endothelial cell differentiation, and KSHV (such as BACH1, xCT, MAF, and others) have been individually validated (132)(133)(134). These are by no means the only targets, and it is anticipated that additional targets will be identified in the future.…”
Section: Viral Mirnas Support Viral Infection and Latent Persistencementioning
confidence: 99%
“…In the case of KS, as malignancy it was early reported in HIV-infected patients since the first cases in 1982; oxidative stress is suggested to interact with all multistage process of this coinfection, i.e., initiation, promotion, and progression [17]. How oxidative stress is involved in these various steps is the object of revision and investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Data that support the contribution of oxidative stress in AIDS-KS pathogenesis has also been accrued at the cellular biochemical level [16][17][18][19]. In vitro studies conducted by Ye et al showed that AIDS-KS strains demonstrate enhanced susceptibility to oxidative stress as induced by either physiologically relevant levels of hydrogen peroxide [18] or conducted by Li et al who show activation through a drug capable of undergoing redox cycling (doxorubicin) [19].…”
Section: Multivariate Discriminant Analysis Of Redox and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In suppressing BACH1, the membranebound subunit of the amino acid transporter xCT increases, thus intracellular glutathione stores remain full providing protection against oxidative stress. Further, xCT is the cell surface receptor for the entry of KSHV (454). The Orf63 of KSHV is homologous to the cellular NLR (nucleotide binding and oligomerization, leucinerich repeat), which activates innate immune reactions in the inflammasome.…”
mentioning
confidence: 99%